Modeling and Analysis of a High-Displacement Pneumatic Artificial Muscle With Integrated Sensing - Yang, Hee Doo; Greczek, Brandyn T.; Asbeck, Alan T. (Frontiers in Robotics and AI, 2019)
We present a high-displacement pneumatic artificial muscle made of textiles or plastics that can include integrated electronics to sense its pressure and displacement. Compared to traditional pneumatic muscle actuators such as the McKibben actuator and other more recent soft actuators, the actuator described in this paper can produce a much higher (40~65%) contraction ratio. In this paper, we describe the design, fabrication, and evaluation of the actuator, as well as the manufacturing process used to create it. We demonstrate the actuator design with several examples that produce 120N and 300N at pressures of 35kPa and 105kPa, respectively, and have contraction ratios of 40% to 65%.